Pengenalan Aplikasi Augmented Reality Sebagai Media Pembelajaran Konstruksi Bangunan Berbasis Android - Rahmad Kurniawan; Muhammad Luthfi Hamzah; Tengku Khairil Ahsyar; Eki Saputra; Syaifullah Syaifullah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Augmented Reality is a technology that combines virtual objects into a real environment and then projects these differences at the same time. The application of ICT-based teaching (Information, Communication and Technology) or better known as TIK (Technology, Information and Communication) at SMKN 2 Pekanbaru which supports various IT-related means starting from Network, Software and Hardware. Especially in the building drawing engineering major, the use of IT is good enough to support learning, such as software that supports CAD programs. In addition, SMKN 2 Pekanbaru also has supporting hardware such as computers, laptops and tablets. Based on this, the creation of building construction augmented reality applications as an innovative and interesting learning media can make maximum use of the school facilities that have been provided. This study uses the Agile method as an application design method that focuses on advanced development and Unity 3D as software in building construction augmented reality applications, As well as the Vuforia SDK as a device that allows the creation of augmented reality applications. This study also uses the black box and system usability scale (SUS) with the Category “Good” of 70.075% as a method of application testing that produces an evaluation of learnability of 96%, efficiency matrix of 0.001/SEC, and error metrix of 0.11.